Oxidative Stress in the Protection and Injury of the Lacrimal Gland and the Ocular Surface: are There Perspectives for Therapeutics? - Lemos, Camila Nunes; Silva, Lilian Eslaine Costa Mendes da; Faustino, Jacqueline Ferreira; Fantucci, Marina Zilio; Murashima, Adriana de Andrade Batista; Adriano, Leidiane; Alves, Monica; Rocha, Eduardo Melani (Frontiers in Cell and Developmental Biology, 2022)
Oxidative stress (OS) is a major event in the physiology of the lacrimal functional unit (LFU). Antioxidant enzymes have dual protective activity: antioxidant and antimicrobial. Peroxidases have been indistinctly used as markers of secretory activity of the LFU and implicated in the pathophysiology, diagnosis and treatment of dry eye disease (DED); even though they comprise a large family of enzymes that includes lactoperoxidase (LPO) and glutathione peroxidase (GPO), among others. Assays to measure and correlate OS with other LFU local phenomena have methodological limitations. Studies implicate molecules and reactions involved in the OS as marker of homeostasis and other studies identify them as part of physiopathology of diseases. Despite of these conflicting concepts and observations it is clear that OS takes part in DED. Moreover, many antioxidant strategies are proposed for its treatment, from calorie restriction to nutritional supplementation. This review offers a critical analysis of the biological mechanisms, diagnostic endpoints, drugs, dietary supplements, and life habits that implicate OS with DED.